Current state of industrial heating and opportunities for decarbonization. (July 2022) - Pisciotta, Maxwell; Pilorgé, Hélène; Feldmann, John; Jacobson, Rory; Davids, Justine; Swett, Shelvey; Sasso, Zachary; Wilcox, Jennifer
Abstract: The IPCC recommends keeping the global average temperature increase well below 2 °C, if not below 1.5 °C, by 2100 to avoid the worst effects of climate change. This requires achieving carbon neutrality shortly after 2050. In the United States, industrial emissions represent 22% of greenhouse gas emissions and are particularly hard to decarbonize, because (1) the processes emit CO2 as a byproduct of chemical reactions and (2) these industries require high-grade heat input. This study focuses on some of these industries, namely cement, lime, glass, and steelmaking. This work details the incumbent kiln and furnace technologies and explores the developing processes with examples of existing projects that aim to reduce carbon emissions, such as carbon capture and storage (CCS), fuel switching, and other technological changes. We provide tools to evaluate the most appropriate low-carbon solutions at existing facilities and on new-build infrastructure while taking into account the local context and resources. This paper highlights two states within the U.S. with a high concentration of cement, lime, glass, and steelmaking facilities, California and Pennsylvania. The emissions from cement, lime, and glass facilities in California total 8.5 MtCO2 eq/yr. About 6.3 MtCO2 /yr (7.1% of in-state industrial emissions) could be captured from cement and lime facilities, transported, and stored in sedimentary basins below the Central Valley. Replacing 20% of coal by biomass could also reduce the fossil emissions by 0.5 MtCO2 /yr (6.2% of in-state industrial emissions) without making changes to the facilities. In Pennsylvania, heavy industry (cement, lime, glass, and steelmaking) emits about 9.4 MtCO2 eq/yr. Most of the facilities are located near sedimentary basins, facilitating the development of CCS. In addition, the presence of low-carbon energy sources can help in the deployment of electrified processes. Also, industrial byproducts such as steel slag and fly ash can be reused in low-carbon concrete mix. As shown with these two examples, there are many strategies leading to the deep decarbonization of the economy and they need to be adapted to the local context.